Stability of periodic clusters in globally coupled maps - Panchuk, A.A.; Maistrenko, Y.L. (Нелінійні коливання, 2002)
The phenomenon of partial synchronization, — or clustering, — in a system of globally coupled C 1 - smooth maps is analyzed. We prove stability of equally populated K-clustered states with period-n temporal dynamics, referred to as PnCK-states. For this, we first obtain formulas giving relation between longitudinal and transverse nultipliers of the in-cluster periodic orbits and then, using these formulas, find exact parameter intervals for the transverse stability. We conclude that typically, for the symmetric PnCK-states, in-cluster stability implies transverse stability. Moreover, transverse stability can take place even if the incluster dynamics is unstable. Проводиться аналiз явища часткової синхронiзацiї, або кластеризацiї, в системi глобально зв’язаних вiдображень гладкостi C 1 . Розглядаються K-кластернi стани з n-перiодичною динамiкою, якi називаються PnCK-станами, i доводиться їх стiйкiсть. Для цього спочатку отримано формули, що пов’язують поздовжнi та трансверсальнi мультиплiкатори кластеризованих перiодичних орбiт, а потiм з допомогою цих формул знайдено точнi межi iнтервалiв для трансверсальної стiйкостi. Зроблено висновок, що для симетричних PnCK-станiв iз стiйкостi всерединi кластера випливає стiйкiсть трансверсальна. Бiльше того, навiть у випадку, коли динамiка всерединi кластера нестiйка, трансверсальна стiйкiсть може мати мiсце